TINJAUAN ETIKA BISNIS ISLAM DALAM STRATEGI PEMASARAN BUSANA MUSLIM DI TOKO PURNAMA STORE MUARA SABAK BARAT KABUPATEN TANJUNG JABUNG TIMUR - Hanna Fadhila Syahira, Siti; Daud, Daud; Edi Saputra, Ahmad; Wandi (Jurnal Dinamika Ekonomi Syariah, 2025)
Marketing strategy is a series of business steps designed at the product presentation stage to attract consumer interest in buying the product. In addition to attracting consumer attention to buy, marketing strategy also aims to ensure that consumers understand the products offered, verify their quality, and encourage repeat purchases. This study uses a field approach with a qualitative descriptive method. Data collection was carried out through observation, interviews, and documentation. The data collected was then analyzed to answer the research problems. The purpose of this study was to identify the marketing strategies implemented by Toko Purnama Store Muara Sabak. The results showed that Toko Purnama Store Muara Sabak has an effective defensive marketing strategy, with a variety of products, both from big and local brands, as well as adequate services and has undergone training. The pricing of goods is based on the policies of the central big brand and local market prices for local products. Promotion is carried out through social media such as WhatsApp, Facebook, TikTok, live streaming, and Instagram. Islamic values are applied in store operations, which can be seen from the obligation of employees to wear gamis and hijab uniforms, as well as the requirement for employees to be Muslim.